Paleozoic corals of Alaska. (Washington, D.C. Government Printing Office, 1975)
Contents: Churkin, M., Jr. Geologic and paleogeographic setting of Paleozoic corals in Alaska.Oliver, W. A., Jr., Merriam, C. W. and Churkin, M., Jr. Ordovician, Silurian, and Devonian corals of Alaska.Armstrong, A. K. Carboniferous corals of Alaska.Rowett, C. L. Stratigraphic distribution of Permian corals in Alaska.
Keywords: Paleontology; Corals, Fossil